2008
DOI: 10.1007/s12253-008-9013-4
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Chemotherapy-induced Cardiomyopathy: a Prospective Tissue Doppler Imaging Study

Abstract: The aim of our study was to compare the applicability of the conventional echocardiography and a novel method, tissue Doppler imaging (TDI) in detection of late or subclinical cardiotoxicity following anthracycline chemotherapy in long-term follow up. Forty women (31 to 65 years) were enrolled, who had not received anthracyclines previously and had normal cardiac function. The control group consisted of 20 healthy persons of similar age range. In addition to standard echocardiographic measurements, each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 31 publications
4
24
0
2
Order By: Relevance
“…Several investigators have demonstrated an early reduction in e ′ velocity of the mitral annulus in patients receiving anthracyclines ( Figures 7C and 7D), 48,[150][151][152] which remained reduced during treatment 153 and for several years thereafter. 150 The reductions in e ′ velocity appear heterogeneous, 150,151,154 suggesting differences in regional wall stress, apoptosis, or fibrosis.…”
Section: Detection Of Sub-clinical LV Dysfunction Using Dti Velocitiesmentioning
confidence: 99%
“…Several investigators have demonstrated an early reduction in e ′ velocity of the mitral annulus in patients receiving anthracyclines ( Figures 7C and 7D), 48,[150][151][152] which remained reduced during treatment 153 and for several years thereafter. 150 The reductions in e ′ velocity appear heterogeneous, 150,151,154 suggesting differences in regional wall stress, apoptosis, or fibrosis.…”
Section: Detection Of Sub-clinical LV Dysfunction Using Dti Velocitiesmentioning
confidence: 99%
“…The applicability of the conventional and tissue Doppler echocardiography for detection of late or subclinical cardiotoxicity, following anthracycline chemotherapy was compared in forty women (Nagi et al, 2008). After one year diastolic left ventricular function was impaired in 97.5% of patients, and in 25% of them diastolic dysfunction could only be detected with TDI.…”
Section: Pulsed-wave Tissue Doppler Imagingmentioning
confidence: 99%
“…Disfunção diastólica por toxicidade cumulativa dosedependente pode ser observada com dose cumulativa equivalente a 200 mg/m 2 , enquanto disfunção sistólica é observada usualmente com doses acima de 400 mg/m 2 , com variabilidade segundo limiar individual 19 . Entretanto, prejuízo na função diastólica foi observado com dose cumulativa de apenas 120 mg/m 2 20 .…”
Section: -Antraciclinasunclassified